2006
DOI: 10.1063/1.2362981
|View full text |Cite
|
Sign up to set email alerts
|

Separate domain formation in Ge2Sb2Te5–SiOx mixed layer

Abstract: We report separate domain formation in cosputtered Ge2Sb2Te5–SiOx mixed layer, with SiOx amount less than 10mol%. As-prepared Ge2Sb2Te5–SiOx layer exhibits amorphous phase with separate domains smaller than 20nm. The separation maintains after thermal annealing, which results in crystallization into fcc phase. The crystallization activation energies of Ge2Sb2Te5–SiOx are obtained as 4.99 and 6.44eV for mixed layers containing 5.3 and 8.4mol% SiOx, respectively. Those are larger than 2.75eV of pure Ge2Sb2Te5. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Therefore, the nitride film significantly inhibits the diffusion of atoms and increases the endurance of materials. Similar results were obtained when adding a few percent of SiO x to GST [90,91]. It was shown that doping increases GST resistivity by several orders of magnitude and significantly decreases the thermal conductivity of the fcc phase.…”
Section: Physics Of Switching and Memory Effects 569supporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, the nitride film significantly inhibits the diffusion of atoms and increases the endurance of materials. Similar results were obtained when adding a few percent of SiO x to GST [90,91]. It was shown that doping increases GST resistivity by several orders of magnitude and significantly decreases the thermal conductivity of the fcc phase.…”
Section: Physics Of Switching and Memory Effects 569supporting
confidence: 80%
“…This allows a sig nificant decrease in the write pulse current [71]. The properties of doped Ge 2 Sb 2 Te 5 were studied in [87][88][89][90][91][92][93]. The most interesting results were obtained by doping with nitrogen.…”
Section: Physics Of Switching and Memory Effects 569mentioning
confidence: 99%
“…Therefore, the crystallization temperature can be defined as the temperature at which the first derivative of the sheet resistance with respect to temperature reaches a minimal value. The [GeTe (5 nm)/Ge 2 Sb 2 Te 5 (5 nm)] 10 and [GeTe (7 nm)/Ge 2 Sb 2 Te 5 (5 nm)] 8 multilayer films clearly showed the abrupt drop of sheet resistance at about 188 and 197 C, respectively. Obviously, the crystallization temperatures of the multilayer films will approach that of GeTe with increasing thickness ratio of GeTe to Ge 2 Sb 2 Te 5 due to the higher crystallization temperature of GeTe over Ge 2 Sb 2 Te 5 .…”
Section: Resultsmentioning
confidence: 97%
“…To evaluate the electrically induced switching characteristics of GeTe/Ge 2 Sb 2 Te 5 multilayer films, PCM devices were fabricated and tested using 100-nm-thick [GeTe (5 nm)/Ge 2 Sb 2 Te 5 (5 nm)] 10 . The PCM with Ge 2 Sb 2 Te 5 was also fabricated for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation